COMPARING THE INCOMPARABLE:: CAN THE EUROPEAN UNION PROVIDE A MODEL FOR REGIONAL INTEGRATION FOR THE MIDDLE EAST? (Journal of European Studies (JES), 2015)
Comparing the European Union and other regional integration experiences in the world, including the Middle East, seems logical and relevant in order to better understand the phenomenon of regionalization. However, such comparison must be separated from the question whether the European model should, or could, be applied universally.